Determine Marketing Strategies Using SWOT Analysis in The MSME Creative Industry to Design Mock-Up Products - Maharani, Rieska; Mukhlis, Imam (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
The MSME creative industry has a significant role in local and national economic activities. Creative products from MSMEs provide added value and innovation, create jobs, and support economic growth. MSMEs often face challenges in marketing their products. In increasingly fierce competition, it is important to develop effective marketing strategies. Geographical boundaries are no longer limits today's creative industries. MSMEs in this sector must face competition not only in regional areas but also on a national scale. The research method used in this article is a descriptive qualitative method with a SWOT analysis approach. This research can analyze MSME marketing strategies in the creative industry and become a new contribution to literature and business practices. It is hoped that this research can also provide insight and practical recommendations to MSMEs in the creative industry, the government, and other related parties to increase the competitiveness and growth of the creative industry by using all marketing media and doing it consistently